THE COSTS ASSOCIATED WITH THE RESISTANCE MOVEMENT FROM TRACK - Lipovskyi, R. S.; Umanov, M. I.; Gubar, O. V.; Chernyshova, O. S. (Science and Transport Progress, 2009)
The procedure of determination of expenses related to the resistance to movement due to the track is presented.